IMPLEMENTATION OF DISCOVERY LEARNING MODELS TO IMPROVE THE ABILITY OF SOLVING PROBLEMS AND LEARNING ACHIEVEMENTS (Study on Chemistry Subject Class XII Students in Senior High School 1 Tebing Tinggi) - Mira Titi Sumanty; Turdjai Turdjai (DIADIK, 2018)
This study aims to describe the application of discovery learning models to improve the solving problem ability, and student learning achievement, and describe the effectiveness of the implementation of discovery learning models can improve student learning achievement. This study uses the Classroom Action Research method followed by true experiments. The subjects of this study were students of class XII MIPA 1 in SMA 1 Tebing Tinggi. Data collection techniques used were observation and test sheets. Qualitative data were analyzed inductively and quantitative data were analyzed quantatively using the average formula and t test. The results of this study conclude that the application of the discovery learning model can improve students' ability to solve problems and student achievement, and effectively improve student achievement in class XII MIPA.1 in SMA 1 Tebing Tinggi